Development of a novel colorimetric immunoassay for C-Reactive Protein using colloidal nanoparticles - Tjitra, Niklas Lesmana (2019)
C-Reactive Protein is an inflammation marker that is known as an early indicator of a wide range of diseases. Most importantly, it predicts the risk of future cardiovascular medical events in serum concentrations of 0.1 to 10 µg mL-1. Simple colorimetric CRP assays are of great interest for application in point-of-care diagnostics. In this project, colorimetric gold nanoparticle assays based on local surface plasmon coupling phenomena were developed using anti-CRP antibodies and affimer proteins. ELISA experiments were first performed to confirm the binding of antibodies and affimer proteins to CRP. Antibody-functionalized Au NPs were then developed, but showed poor sensitivity and specificity. QCM data demonstrated the feasibility of sandwich binding, and suggested that the antibody-functionalized Au NPs exhibited distance decay of the plasma coupling. Affimer-functionalized Au NPs were developed, and showed specific binding to CRP. Colour changes in the assay from pinkish red to violet were observed and scaled with increasing CRP concentration. Upon CRP spiking at 1 µg mL-1, affimer-functionalized Au NPs showed improvement in sensitivity, and the LOD was calculated to be 0.2 µg mL-1. Au NP aggregation against CRP concentration was plotted and fitted to a linear calibration curve, and the correlation was shown to be statistically significant. The dynamic range of the assay extended from 0.2 µg mL-1 to beyond 10 µg mL-1, making it suitable for use as a risk predictor for cardiovascular disease.